Towards world class academic librarie LibFe 2006 : Conference on Libraries for the Future, 25-26 April 2006, Grand Blue Wave Hotel Shah Alam - Conference on Libraries for the Future (2006 : Shah Alam); Universiti Teknologi MARA. Perpustakaan Tun Abdul Razak (Shah Alam : Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA, 2006)
Contained 8 work papers of Conference on Library For The Future in PDF format
System requirement : Adobe Acrobat Reader
Keywords: Academic libraries -- Congresses; Library science -- Congresses